1974
DOI: 10.1113/jphysiol.1974.sp010631
|View full text |Cite
|
Sign up to set email alerts
|

Differential reaction of fast and slow α‐motoneurones to axotomy

Abstract: SUMMARY1. The properties of medial gastrocnemius (m.g., fast a) and soleus (sol., slow a) motoneurones of the cat were examined with intracellular electrodes 8-119 days after section of the muscle nerves.2. The axonal conduction velocity was significantly decreased in both m.g. and sol. motoneurones after chronic section of the muscle nerves.3. The amplitude of overshoot of action potentials was significantly increased in both m.g. and sol. motoneurones following section of the muscle nerves.4. No significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
80
0

Year Published

1981
1981
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(92 citation statements)
references
References 28 publications
12
80
0
Order By: Relevance
“…Autologous grafts typically originate from the patient's sural nerve (a nerve in the lower leg) or other sensory nerves. Since autografts continue to 15 provide the best clinical results, as a natural biomaterial they are considered the "gold standard" in peripheral nerve repair, and the associated functional losses elsewhere in the body are often regarded as acceptable. Nevertheless, major advances in the understanding of nerve regeneration, in surgical techniques, and in material design are producing ever improving alternatives to autologous nerve grafts.…”
Section: Autologous Nerve Graftsmentioning
confidence: 99%
“…Autologous grafts typically originate from the patient's sural nerve (a nerve in the lower leg) or other sensory nerves. Since autografts continue to 15 provide the best clinical results, as a natural biomaterial they are considered the "gold standard" in peripheral nerve repair, and the associated functional losses elsewhere in the body are often regarded as acceptable. Nevertheless, major advances in the understanding of nerve regeneration, in surgical techniques, and in material design are producing ever improving alternatives to autologous nerve grafts.…”
Section: Autologous Nerve Graftsmentioning
confidence: 99%
“…Last, changes in the types of channels expressed may reflect an injury-induced de-differentiation process (Cummins and Waxman 1997;Kuno et al 1974;Waxman et al 1994). In other words, "large" cells tend to acquire the characteristics of "small" cells and vice versa.…”
Section: General Trends In the Datamentioning
confidence: 99%
“…Czeh and colleagues (Czeh, Gallego, Kudo & Kuno, 1978) demonstrated that tetrodotoxin (TTX)-induced muscle paralysis, like axotomy, resulted in decreased duration of the action potential after-hyperpolarization (AHP) in cat soleus motoneurons, coincident with muscle atrophy, and that stimulation of the motor axons distal to the TTX block prevented these changes. They concluded that 'it is likely that muscle activity is directly or indirectly signalled to the innervating motoneurons through the motor axons' (Czeh et al 1978 (Kuno et al 1974a;Gustafsson & Pinter, 1984), muscle inactivity induced by pharmacological nerve blockade with TTX for similar time periods has resulted in axotomy-like (Munson, Foehring & Sypert, 1985) or normal motoneurons (Webb & Cope, 1992 Gardiner, Favron & Corriveau, 1992;Michel, Cowper, Chi, Manchester, Falter & Lowry, 1994). We chose to measure responses over a 2 week period as this duration of inactivity appears to be sufficient for motoneuron changes to occur (Czeh et al 1978;Munson et al 1985).…”
mentioning
confidence: 99%